SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK DI SMK NEGERI 6 PADANG DENGAN METODE ANALYTICAL HIERARCHY PROCESS AHP - Yarri, Reka; Mary, Thomson; Samudra, Ami Anggraini Samudra (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to develop a decision support system in selecting the best teachers at SMK Negeri 6 Padang using the Analytical Hierarchy Process (AHP) method. Teachers have an important role in the world of education, so that selecting the best teachers is a crucial aspect in improving the quality of learning. This system is designed to provide recommendations based on several predetermined assessment criteria. With the implementation of AHP, the system can provide objective weights and rankings for each candidate, so that the selection process becomes more transparent and accurate.   The research method used includes the System Development Life Cycle (SDLC) approach with an iterative model, which consists of planning stages, needs analysis, system design, implementation, testing and evaluation. System design is carried out using Unified Modeling Language (UML), while testing is carried out using black box and white box testing methods to ensure the system runs according to the specified specifications. The research results show that this system can help schools determine the best teachers more effectively and efficiently.   It is hoped that this system can be a solution for schools in making data-based decisions, reducing subjectivity in teacher assessments, and increasing the motivation and performance of teaching staff.